Deepening EU-Ukrainian Relations : What, Why and How?. - Emerson, Michael (Rowman & Littlefield International, 2016)
This handbook explains in readily comprehensible language what the new Association Agreement and its Deep and Comprehensive Free Trade Area (DCFTA) between the European Union and Ukraine means in legal, political and economic terms. This treaty is a milestone in the history of Ukraine's place in Europe, and definitively marks the country's post-Soviet independence. It is also a new model treaty for the EU's relations with its closest neighbours.